2013
DOI: 10.1039/c2ta00839d
|View full text |Cite
|
Sign up to set email alerts
|

A two-electron mechanism of lithium insertion into layered α-MoO3: a DFT and DFT+U study

Abstract: We study the changes in electrodynamic responses due to Li insertion into layered a-MoO 3 . We compute electronic and dielectric properties, including the optical conductivity response of pure and lithiated oxides Li 2 MoO 3 , as a means to understand and reproduce the charge-discharge profiles observed in experiments.We unravel a 2-electron mechanism of Mo(VI) center reduction, which suggests Li substitution by divalent cations as a route towards cycling optimization. Along this line we provide a general para… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
32
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 36 publications
(57 reference statements)
5
32
0
Order By: Relevance
“…Studies that xed the b-axis reported higher bandgaps of between 1.95 eV 61 and 2.4 eV, 47 in line with results showing that lattice distortion has a signicant effect on bandgap. 79 It has been shown that adding a +U correction only widens the computed gap by around 0.1 eV or so, 51,52 while the use of the HSE06 hybrid functional produces bandgaps consistent with experimental value, 47,48,85 at the cost of greatly increasing computational complexity.…”
Section: Model Vericationmentioning
confidence: 94%
“…Studies that xed the b-axis reported higher bandgaps of between 1.95 eV 61 and 2.4 eV, 47 in line with results showing that lattice distortion has a signicant effect on bandgap. 79 It has been shown that adding a +U correction only widens the computed gap by around 0.1 eV or so, 51,52 while the use of the HSE06 hybrid functional produces bandgaps consistent with experimental value, 47,48,85 at the cost of greatly increasing computational complexity.…”
Section: Model Vericationmentioning
confidence: 94%
“…A wide variety of Ueff values falling in the range of 1-8.3 eV has been used in the literature. 57,[59][60][92][93][94][95][96] The value of Ueff depends on the quantities being fitted since it is unlikely that one can find a value of Ueff that will give correct results for all measurable properties. Here we are interested in computing total energies and we chose 100,102 Ueff to fit the energy of the Figure 4d suggests that MoO2 is anti-ferromagnetic, whereas experiments near room temperature suggest MoO2 is Pauli-paramagnetic.…”
Section: Estimation Of Ueffmentioning
confidence: 99%
“…This leads to upgraded electrical conductivity, while on the other hand causes a decrease in specific charge. It is noteworthy, however, that pre-lithiation may yield a totally new class of advanced cathode materials with high specific charge such as LiMoO 3 and Li 2 MoO 3 , as also shown by DFT calculations [9].…”
Section: Introductionmentioning
confidence: 96%